International GAAP 2012 : generally accepted accounting practice under international financial reporting standards - Baltazar, Elizer; The International Financial Reporting Group of Ernst & Young (Chichester, West Sussex, U.K., 2012)
International GAAP is the leading and most comprehensive guide to interpreting and implementing IFRS. For accountants and auditors globally, it delivers guidance in addressing IFRS issues as they occur, in addition to being an invaluable resource when preparing interim and annual accounts.
Volume 1 1 International GAAP 1 2 The IASB's Conceptual Framework 39 3 Presentation of financial statements and accounting policies 69 4 Non-current assets held for sale and discontinued operations 139 5 First-time adoption 169 6 Consolidated financial statements (IAS 27) 319 7 Consolidated financial statements (IFRS 10) 355 8 Consolidation procedures and non-controlling interests 451 9 Separate and individual financial statements 505 10 Business combinations 559 11 Common control business combinations 679 12 Associates 713 13 Joint ventures (IAS 31) 809 14 Joint arrangements (IFRS 11) 867 15 Disclosure of interests in other entities 937 16 Fair value measurement 987 17 Foreign exchange 1085 18 Hyperinflation 1151 19 Intangible assets 1187 20 Property, plant and equipment 1271 21 Investment property 1319 Index of extracts from financial statements index 1 Index of standards index 7 Index index 79 Volume 2 22 Impairment of fixed assets and goodwill 1373 23 Capitalisation of borrowing costs 1469 24 Inventories 1491 25 Construction contracts 1511 26 Leases 1535 27 Government grants 1621 28 Service concession arrangements 1637 29 Provisions, contingent liabilities and contingent assets 1683 30 Revenue recognition1765 31 Income taxes 1857 32 Share-based payment 1987 33 Employee benefits 2221 34 Operating segments 2307 35 Earnings per share 2341 36 Events after the reporting period 2405 37 Related party disclosures 2421 38 Statement of cash flows 2457 39 Interim financial reporting 2501 40 Agriculture 2575 41 Extractive industries 2605 Index of extracts from financial statements index 1 Index of standards index 7 Index index 79 Volume 3 42 Financial instruments: Introduction 2839 43 Financial instruments: Definitions and scope 2857 44 Financial instruments: Derivatives and embedded derivatives 2891 45 Financial instruments: Financial liabilities and equity 2933 46 Financial instruments: Classification (IAS 39) 3035 47 Financial instruments: Classification (IFRS 9) 3059 48 Financial instruments: Recognition and initial measurement 3097 49 Financial instruments: Subsequent measurement 3119 50 Financial instruments: Derecognition 3203 51 Financial instruments: Hedge accounting 3283 52 Financial instruments: Presentation and disclosure 3403 53 Insurance contracts 3503 Index of extracts from financial statements index 1 Index of standards index 7 Index index 79
"The International Financial Reporting Group of Ernst & Young"--Cover.
Includes indexes
oif 04/06/14
Loan
Keywords: International financial reporting standards; Accounting -- standards; Financial statements